The Occurrence of the Day-of-the-Week Effects on Polish and Major World Stock Markets - Jamróz, Paweł; Koronkiewicz, Grzegorz (Studies in logic, grammar and rhetoric : the Journal of University of Bialystok, 2014)
The aim of this paper is to analyze the occurrence of the so called day of the week effects in market return time series from the period of January 2003 to September 2013 (and additionally January 1999 to December 2002). The study focuses on four indices of the Warsaw Stock Exchange (WIG, WIG20, mWIG40 and sWIG80) and additionally five indices of major world stock exchanges (NIKKEI 225, DAX, CAC40, S&P 500, and IBEX). The main data sample was divided into three subperiods in order to determine whether or not the intensity of day of the week anomalies is constant in time. The study revealed a substantial number of the day of the week anomalies in earliest subperiods and very limited evidence of those effects in later ones, giving rise to the conclusion that the intensity of the day of the week anomalies is diminishing with time. The most common effect identified on the WSE was a positive Friday effect. The Monday effect often described in early literature on the subject matter seems to currently occur very rarely. The study also indicates that the day of the week effects were more persistent among stocks with smaller market capitalization on the WSE.